Círculos de estudio y redes de aprendizaje colaborativo: Transformación de las prácticas pedagógicas docentes. - Fuentes Rendón, Mercy Karina; Balladares Atoche, César; Cerezo Segovia, Badie Anneriz; Cervantes Garcia, Angela Villy (Editorial Grupo AEA, 2026)
The overall objective of the book is to determine the impact of study circles and learning networks on strengthening teachers' pedagogical skills. The research was conducted with a population of 99 teachers and a sample of 79 teachers from educational institutions working in early childhood and preparatory education in district 12D03. The methodology used was a non-experimental, propositional-explanatory transactional design. The instruments used to collect the information were surveys and questionnaires on the dependent variable of study circles and learning networks. The dimensions (teamwork, social interaction) and indicators (quality of education, educational leadership) were worked on, as well as the independent variable of pedagogical strengthening of teachers, dimensions (social interaction), and indicators (educational leadership, triadic reciprocity). The overall results of the research showed that study circles and learning networks that are enhanced with early childhood teachers are at a low level according to the statistical data analyzed and based on the opinion of the respondents in different dimensions in relation to planning, organization, and teaching practice. The training received suffers from limitations, as there is no constant monitoring and evaluation to determine whether they are being applied, working, and improving teaching and learning processes. Consequently, it can be concluded that, although there is a relationship between variables, there is a need to improve teachers' attitudes and performance in the classroom.